Positioning human body models for crashworthiness using model order reduction. Issue 11 (17th August 2020) - Bacquaert, G.; Bach, C.; Draper, D.; Peldschus, S.; Duddeck, F.
Abstract: A new technique to accelerate the positioning of human body models (HBMs) by means of a dimensionality reduction of a database of precomputed simulations is presented. First, a set of important subspace deformation modes which are used to approximate the model's movements observed in the training simulations are computed. In the second step, a convex optimization problem is solved in order to obtain an optimal position of the human body model as described by the user. We apply the proposed method to a new reclined seating position of the Total Human Model for Safety (THUMS, v5).